2015
DOI: 10.1021/acsami.5b00498
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanoparticles as Modifiers for Rheology and Fluid Loss in Bentonite Water-based Fluids

Abstract: Rheological and filtration characteristics of drilling fluids are considered as two critical aspects to ensure the success of a drilling operation. This research demonstrates the effectiveness of cellulose nanoparticles (CNPs), including microfibrillated cellulose (MFC) and cellulose nanocrystals (CNCs) in enhancing the rheological and filtration performances of bentonite (BT) water-based drilling fluids (WDFs). CNCs were isolated from MFC through sulfuric acid hydrolysis. In comparison with MFC, the resultant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
236
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 316 publications
(242 citation statements)
references
References 53 publications
4
236
2
Order By: Relevance
“…Finally, they noticed that the API fluid loss of PAC/CNCs/bentonite water based drilling fluids remarkably decreased as the concentrations of bentonite and PAC increased, while CNCs had little impact on the fluid loss of the PAC/CNC/bentonite fluid. Li et al [39] explored the effectiveness of cellulose nanoparticles (CNPs), including microfibrillated cellulose (MFC) and CNCs in enhancing the rheological and filtration performance of bentonite water-based drilling fluids. They found that addition of MFC and CNCs increased the rheological properties of bentonite water based drilling fluids, including the viscosity and yield point, demonstrating their capability on improving cuttings transport capacity.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Finally, they noticed that the API fluid loss of PAC/CNCs/bentonite water based drilling fluids remarkably decreased as the concentrations of bentonite and PAC increased, while CNCs had little impact on the fluid loss of the PAC/CNC/bentonite fluid. Li et al [39] explored the effectiveness of cellulose nanoparticles (CNPs), including microfibrillated cellulose (MFC) and CNCs in enhancing the rheological and filtration performance of bentonite water-based drilling fluids. They found that addition of MFC and CNCs increased the rheological properties of bentonite water based drilling fluids, including the viscosity and yield point, demonstrating their capability on improving cuttings transport capacity.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Xuan et al (2014) investigated the graphite oxide nanoparticles and showed it has a strong ability in controlling fluid loss of drilling fluid. Li et al (2015b) used cellulose nanoparticles to improve the rheological properties and fluid loss in water-based drilling fluid and reported. Benyounes et al (2010) investigated the effect of anionic polymer such as carboxymethyl cellulose and xanthan on rheology of bentonite suspension at different concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been shown that CNF-bentonite dispersions display properties suitable for use as drilling fluids (Li et al 2015). However, comprehensive studies on the steady-shear and viscoelastic properties of such CNF-nanoclay dispersions are rare, and previous rheological studies have mainly focused on dispersions of plate-like nanoclays and moderately charged or uncharged nanocellulose particles (Abend and Lagaly 2000;Li et al 2015;Ming et al 2016;Nechyporchuk et al 2014).…”
Section: Introductionmentioning
confidence: 99%